Modeling of Cloud Surveillance System - Diatlov, Ie.I. (Математичні машини і системи, 2016)
The article is devoted to the Cloud Surveillance. The author describes global distributed structure of surveillance system and its main components. The article highlights the main points concerning the processing of video and distributed data storage model. The paper describes main abilities to spread the load among equivalent system services. The author underlines the importance of database replications and backup. This article describes the basic service delivery models of data centers and their positioning relative to the cloud video surveillance applications. Стаття присвячена тематиці хмарного відеоспостереження. Автором описуються глобальна розподілена структура системи і її основні компоненти. Стаття висвітлює основні моменти щодо обробки відеопотоку і розподіленої моделі зберігання даних, описуються можливості для розподілу навантаження між рівнозначними сервісами системи. Автор підкреслює важливість реплікації бази даних і її резервного копіювання. Стаття описує основні сервісні моделі надання послуг дата-центрами і їх позиціонування щодо завдань хмарної системи відеоспостереження. Статья посвящена тематике облачного видеонаблюдения. Автором описываются глобальная распределенная структура системы, а также ее основные компоненты. Статья освещает основные моменты касательно обработки видеопотока и распределенной модели хранения данных, описываются возможности для распределения нагрузки между равнозначными сервисами системы. Автор подчеркивает важность репликации базы данных и ее резервного копирования. Статья описывает основные сервисные модели предоставления услуг дата-центрами и их позиционирование относительно задач облачной системы видеонаблюдения.